Therapeutic Potential of Lindera obtusiloba: Focus on Antioxidative and Pharmacological Properties - Haque, Md Ezazul (Plants (Basel), 2020)
Lindera obtusiloba (LO) BLUME from the genus Lindera (Lauraceae) is a medicinal herb traditionally used in Southeast Asian countries. Indigenously, extracts of different parts of the plant have been used to improve blood circulation and treat allergy, inflammation, rheumatism, and liver diseases. LO is a rich source of therapeutically beneficial antioxidative phytochemicals, such as flavonoids, butenolides, lignans and neolignans. Moreover, recent studies have unravelled the pharmacological properties of several newly found active constituents of LO, such as anti-inflammatory antioxidants (+)-syringaresinol, linderin A, anti-atherosclerotic antioxidant (+)-episesamin, anti-melanogenic antioxidants quercitrin and afzelin, cytotoxic 2-(1-methoxy-11-dodecenyl)-penta-2,4-dien-4-olide, (2Z,3S,4S)-2-(11-dodecenylidene)-3-hydroxy-4-methyl butanolide, anti-allergic koaburaside, (6-hydroxyphenyl)-1-O-beta-d-glucopyranoside and 2,6-dimethoxy-4-hydroxyphenyl-1-O-beta-d-glucopyranoside and the antiplatelet-activity compound Secolincomolide A. These findings demonstrate that LO can be a potential source of antioxidants and other prospective therapeutically active constituents that can lead to the development of oxidative stress-mediated diseases, such as cardiovascular disorders, neurodegenerative disorders, allergies, inflammation, hepatotoxicity, and cancer. Here, the antioxidant properties of different species of Lindera genus are discussed briefly. The traditional use, phytochemistry, antioxidative and pharmacological properties of LO are also considered to help researchers screen potential lead compounds and design and develop future therapeutic agents to treat oxidative stress-mediated disorders.